So sánh khả năng phóng điện của cặp điện cực Pb-PbO2 trong dung dịch axit metasunfonic và axit floroxilixic - Lan, Ngô Thị; Tú, Doãn Anh; Phát, Đoàn Tiến; Mai Thanh, Đinh Thị (Vietnam Journal of Chemistry, 2016)
The HBF4 and H2SiF6 acids are often used as electrolyte for lead reserves batteries, but these are relatively durable acids and harmful to the environment. Meanwhile CH3SO3H acid is biodegradable to form sulfate ions (SO42-) and carbon dioxide (CO2) in the natural environment, thus it’s more environmentally friendly. This paper presents the results of using CH3SO3H acid as electrolyte for lead batteries in different temperatures, acid concentrations and rate of number of acid moles/number of PbO2 moles, in comparison to H2SiF6 acid. In the some determined conditions, CH3SO3H acid can be use as an electrolyte for lead reserves batteries.The 30 % CH3SO3H solution, rates of number of acid moles/number of PbO2 moles is 5.0 ​​and the working temperature > 20 °C are suitable conditions for using as liquid electrolyte of the reserve battery. While discharging at 30 °C, we received the Ebat. = 1897 mV, the maximum discharge voltage = 1694 mV and discharge time = 251s (with discharge voltages ≥ 1650 mV).